Characterization of volume change and strength behavior of micro-silica and lime-stabilized Cyprus clay - GhavamShirazi, Sandra; Bilsel, Huriye (Springer Heidelberg, 2021)
This study aims to assess the suitability of micro-silica (MS) as an industrial waste to modify the hydro-mechanical behavior of expansive soil in comparison with the use of lime as a traditional stabilizer. Due to limitations associated with soil treatment with calcium-based materials, the effect of lime-micro-silica (LMS) on stabilization of expansive clay was also studied with the aim of reducing the amount of lime consumption. The clay was stabilized with different percentages of lime alone (3% and 5%), MS alone (10% and 20%) and mixtures of LMS (3-10%, 5-10%, 3-20% and 5-20%). Experimental study performed on treated and untreated specimens included the reactivity tests measuring the pozzolanicity of the additives, compaction characteristics and Atterberg limits of mixtures, one-dimensional swell, compressibility, shrinkage, unconfined compressive strength of compacted specimens of different mixtures, as well as X-ray diffraction, scanning electron microscopy and wet chemistry analysis to study the mineralogy, microstructure and chemical composition of specimens. The results showed that the addition of MS alone did not have a significant effect on the stabilization of expansive soil, whereas stabilization with LMS achieved promising results with 10% MS + 3% lime mixture, hence achieving the goals of recycling MS as well as minimizing the amount of lime used. This combination was effective in improving the hydro-mechanical behavior of the clay due to formation of cementitious compounds resulting from pozzolanic reactions between Ca(2+)of lime and SiO(2)of micro-silica.
Keywords: Expansive soil; Lime; Micro-silica; Pozzolanic reaction; Stabilization